The use of triptans as an effective form of migraine treatment – review - Agata Borkowska; Anna Kiełb; Anna Mich; Anna Kaźmierczak; Patrycja Sornek; Wiktoria Izdebska; Igor Pawlak; Radosław Ciesielski; Jakub Stanek; Klaudia Perkowska (Quality in Sport)
Introduction Migraine, a prevalent neurological disorder, is characterized by recurrent episodes of moderate to severe headache, often accompanied by symptoms such as nausea, photophobia, and phonophobia. Triptans, which belong to the class of serotonin 5-HT1B/1D receptor agonists, are integral to the management of migraine, providing prompt relief from symptoms.